Gasoline Production by One-pot Catalytic Conversion of Lignocellulosic Biomass Derived Sugar/Polyol. (August 2015) - Wang, Tiejun; Weng, Yujing; Qiu, Songbai; Long, Jinxing; Chen, Lungang; Li, Kai; Liu, Qiying; Zhang, Qi; Ma, Longlong
Abstract: Gasoline production by one-pot catalytic conversion of biomass derived sugar/polyol was investigated over bifunctional heterogeneous catalyst. Ni@HZSM-5/SG catalyst showed excellent performance of converting sugar/polyol to gasoline. The gasoline yield of 46.94% was obtained. Its composition and properties are similar to petroleum based gasoline. It provides a novel approach for the production of gasoline by one-pot aqueous phase catalytic conversion of sugar/polyol derived from biomass.